PERAN PUSTAKAWAN REFERENSI SEBAGAI SCHOLARLY COMMUNICATION LIBRARIAN - Fadhli, Rahmat; Ilmi, Bachrul (Sekolah Vokasi, Universitas Sebelas Maret, 2023)
Scholarly communication is the process of sharing, disseminating, and publishing research results so that academic content can be made available to the public. This study aims to examine the role of reference librarians in their involvement in supporting scholarly communication. This research was conducted using a qualitative approach with data collection through observation, literature review, and interviews involving one special library librarian. The research data were analyzed using the stages of reduction, coding, conclusion drawing, and interpretation. The results of the study show that the involvement of reference librarians in special libraries in supporting scholarly communication includes (1) providing guidance on writing good scientific papers to researchers, (2) providing journal portals; (3) processing ISSN journals that have not been registered both printed and electronic; (4) disseminating new knowledge in the form of scientific writing from the results of the researchthey manage. The results of the study do not generalize the role of special libraries but rather adjustthe functions of special libraries in managing and disseminating knowledge